Temporal and Spatial Development of Axonal Maturation and Myelination of White Matter in the Developing Brain - Gao, W.; Lin, W.; Chen, Y.; Gerig, G.; Smith, J.K.; Jewells, V.; Gilmore, J.H. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) has been widely used to investigate the development of white matter (WM). However, information about this development in healthy children younger than 2 years of age is lacking, and most previous studies have only measured fractional anisotropy (FA). This study used FA and radial and axonal diffusivities in children younger than 2 years of age, aiming to determine the temporal and spatial development of axonal maturation and myelination of WM in healthy children.MATERIALS AND METHODS: A total of 60 healthy pediatric subjects were imaged by using a 3T MR imaging scanner. They were divided into 3 groups: 20 at 3 weeks, 20 at 1 year of age, and 20 at 2 years of age. All subjects were imaged asleep without sedation. FA and axial and radial diffusivities were obtained. Eight regions of interest were defined, including both central and peripheral WM for measuring diffusion parameters.RESULTS: A significant elevation in FA (P < .0001) and a reduction in axial and radial diffusivities (P < .0001) were observed from 22 days to 1 year of age, whereas only radial diffusivity showed significant changes (P = .0014) from 1 to 2 years of age. The region-of-interest analysis revealed that FA alone may not depict the underlying biologic underpinnings of WM development, whereas directional diffusivities provide more insights into the development of WM. Finally, the spatial development of WM begins from the central to the peripheral WM and from the occipital to the frontal lobes.CONCLUSIONS: With both FA and directional diffusivities, our results demonstrate the temporal and spatial development of WM in healthy children younger than 2 years of age.